Prevalence of large vessel occlusion in patients presenting with acute ischemic stroke: a 10-year systematic review of the literature. (10th November 2018) - Lakomkin, Nikita; Dhamoon, Mandip; Carroll, Kirsten; Singh, Inder Paul; Tuhrim, Stanley; Lee, Joyce; Fifi, Johanna T; Mocco, J
Abstract : Background: Accurate assessment of the prevalence of large vessel occlusion (LVO) in patients presenting with acute ischemic stroke (AIS) is critical for optimal resource allocation in neurovascular intervention. Objective: To perform a systematic review of the literature in order to identify the proportion of patients with AIS presenting with LVO on image analysis. Methods: A systematic review was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines in order to identify studies reporting LVO rates for patients presenting with AIS. Studies that included patients younger than 18 years, were non-clinical, or did not report LVO rates in the context of a consecutive AIS series were excluded. Characteristics regarding presentation, diagnosis, and LVO classification were recorded for each paper. Results: Sixteen studies, spanning a total of 11 763 patients assessed for stroke, were included in the qualitative synthesis. The majority (10/16) of articles reported LVO rates exceeding 30% in patients presenting with AIS. There was substantial variability in the LVO definitions used, with nine unique classification schemes among the 16 studies. The mean prevalence of LVO was 31.1% across all studies, and 29.3% when weighted by the number of patients included in each study. Conclusions: Despite the wide variability in LVO classification, the majority of studies in the last 10 years report a high prevalence of LVO in patients presenting with AIS. These rates of LVO may have implications for the volume of patients with AIS who may benefit from endovascular therapy.